1995
DOI: 10.1046/j.1471-4159.1995.64010292.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postasphyxial Resuscitation with 100% and 21% Oxygen on Cortical Oxygen Pressure and Striatal Dopamine Metabolism in Newborn Piglets

Abstract: The present study tests the hypothesis that ventilation with 100% 02 during recovery from asphyxia leads to greater disturbance in brain function, as measured by dopamine metabolism, than does ventilation with 21 % oxygen . This hypothesis was tested using mechanically ventilated, anesthetized newborn piglets as an animal model . Cortical oxygen pressure was measured by the oxygen-dependent quenching of phosphorescence, striatal blood flow by laser Doppler, and the extracellular levels of dopamine and its meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 43 publications
(45 reference statements)
1
10
0
1
Order By: Relevance
“…Our earlier studies have shown that during hypoxia there was a large increase in the level of striatal extracellular dopamine, followed by a decrease of dopamine almost to the control level during 1 h of post-hypoxic reoxygenation. However, at about 2 h into the post-hypoxia period there was a secondary increase in extracellular dopamine indicating substantial release of dopamine from the neurons [18]. Horiguchi et al [19] reported that hypothermia (32 °C) significantly inhibited the ischemia-induced increase in extracellular dopamine in the striatum of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies have shown that during hypoxia there was a large increase in the level of striatal extracellular dopamine, followed by a decrease of dopamine almost to the control level during 1 h of post-hypoxic reoxygenation. However, at about 2 h into the post-hypoxia period there was a secondary increase in extracellular dopamine indicating substantial release of dopamine from the neurons [18]. Horiguchi et al [19] reported that hypothermia (32 °C) significantly inhibited the ischemia-induced increase in extracellular dopamine in the striatum of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Under these control conditions oxygen pressure levels in the slice tissue were found to be 583 Torr at the upper surface of the tissue and 157 Torr in the core of the slice (Neff et al, 2004). Although these values are higher than brain oxygen pressure found in in-vivo studies (Huang et al, 1995; Song et al, 1997), we have labeled these as normoxia given their widespread use as control conditions for in-vitro electrophysiological experiments. When the solution is equilibrated with 20% O 2 the O 2 tension in the tissue decreases to 142 Torr at the surface and to 0 Torr in the core of the slice and this has been used previously as a model of hypoxia (Neff et al, 2004).…”
Section: Methodsmentioning
confidence: 88%
“…Although similar findings were observed in this study, the use of 100% oxygen following asphyxia did not result in greater cerebral cellular membrane dysfunction in newborn piglets even though free radical generation and energy failure tended to be higher. Other effects on neurotransmitter metabolism have reported a disruption in striatal dopamine metabolism following postasphyxial resuscitation with 100% oxygen [38].…”
Section: Discussionmentioning
confidence: 99%